Radical Questioning on the Long Walk to Freedom: Nelson Mandela and the Practice of Critical Reflection - Stephen Brookfield (Adult Education Research Conference, 2007)
This paper examines the autobiography of Nelson Mandela Long Walk to Freedom. Using a formulation of critical reflection as the deliberate uncovering and challenging of assumptions concerning power and hegemony, Long Walk to Freedom is subjected to a thematic content analysis using the analytical heuristic of critical reflection.